An Evaluation of Tourists’ Intention towards the Sustainable Conservation of Cultural Heritage Destinations: The Role of Place Identity, Destination Image & Sustainable Intelligence - Siddiqui, Samiha; --, Sujood; Bano, Naseem; Hamid, Sheeba (Journal of Tourism, Sustainability and Well-being, 2023)
Cultural heritage tourism is widely acknowledged as one of the main attractions of tourism and the role of various stakeholders in the conservation and sustainable development of these irreplaceable destinations is widely discussed. However, little attention has been paid to the investigation of the tourists’ role in the sustainability of Cultural heritage destinations. Thus, this empirical study looks at the elements influencing tourists’ engagement in the sustainable conservation of cultural heritage destinations. Accordingly, it broadens the Theory of planned behaviour (TPB) by including Place Identity, Destination Image and Sustainable Intelligence as antecedents of Sustainable behaviour. The data is analysed using structural equations modelling with AMOS (V23) and SPSS (V25) software and the suggested hypotheses are statistically verified. The research’s outcomes offer insightful data that may be considered a guide for the sustainable development of cultural heritage destinations. The findings add to a further comprehensive understanding of sustainable heritage management through deeper insight into visitors’ decision-making approach to protecting cultural heritage destinations. The results are instrumental for various tourism and destination marketing organizations, heritage tourism planners, various policymakers, and the government at large.